Good Governance and Modern International Financial Institutions : AIIB Yearbook of International Law 2018 - Quayle, Peter (Brill, 2019)
The first volume of the AIIB Yearbook of International Law (AYIL) examines a series of dimensions to the good governance of modern International Financial Institutions. Readership: All international legal practitioners, academics and students interested in international law, international organizations (including international financial institutions), the Asian Infrastructure Investment Bank generally, and the international legal status and accountability of multilateral institutions, together with good governance.
Keywords: International law